An approach to the numerical studies of partial differential equations (PDEs) - Pang, Keith Jing Jie (2012)
In todays’ engineering practices, numerical methods are integral to the development of solutions for the myriad of engineering problems. The key role that numerical methods play is to come up with approximate solutions to complicated engineering problems with the help of computers using mathematical models or equations so that we are able to understand our problem better.